APLIKASI TANUR SEBAGAI PELEBURAN LOGAM DITINJAU DARI ASPEK K3 (KESELAMATAN DAN KESEHATAN KERJA) - Supriono, Supriono (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2020)
The metal / steel casting industry is an industry that utilizes electrical energy as a heating source to melt metal. The electrical energy used is induction, namely; the effect of a magnetic vortex. The types of furnaces that are commonly used, such as: electric furnaces, induction furnaces, crucible stoves, kupola kitchens, air kitchens and kitchens. Hazard factors arising from the operation of the furnace include: noise, heat pressure, metal vapor, explosion. Keyword: metal smelting industry, induction